IMPACTO DA EMBALAGEM NOS VALORES DOS LIMIARES HEDÔNICOS PARA REDUÇÃO DE CLORETO DE SÓDIO EM BISCOITO SALGADO. - Santanna, Laudiane Justo (2020)
Excessive sodium consumption by the population is a worldwide problem and numerous strategies have been developed to minimize it. The information provided on the packaging can have positive or negative effects on consumer behavior and choices. In this con